MAGNETIC BEHAVIOR OF NICKEL FERRITE NANOPARTICLES PREPARED BY CO-PRECIPITATION ROUTE - Maaz, K.; Mashiatullah, A.; Qazi, N. K.; Javed, T.; Qureshi, R. M.; Karim, S.; Ali, G. (The Nucleus, 2020)
Magnetic nanoparticles of nickel ferrite (NiFe2O4) have been synthesized by co-precipitation route using stable ferric and nickel salts with sodium hydroxide as the precipitating agent and oleic acid as the surfactant. X-ray Diffraction (XRD) and Transmission Electron Microscope (TEM) analyses confirmed the formation of single phase nickel ferrite nanoparticles in the range 8-28 nm. The size of the particles was observed to be increasing linearly with increasing annealing temperature of the sample. Typical blocking effects were observed below ~225 K for all the prepared samples. The superparamagnetic blocking temperature was found to be continuously increasing with increasing particle sizes that has been attributed to the increased effective anisotropy of the nanoparticles. The saturation moment of all the samples was found much below the bulk value of nickel ferrite that has been attributed to the disordered surface spins of these nanoparticles.